THE SHIFTING PARADIGMS IN THE IMPLEMENTATION OF CLT IN SOUTHEAST ASIA COUNTRIES - Martin Kustati (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Foreign languages teachers in South East Asia have recently been encouraged to adopt an approach known as Communicative Language Teaching (CLT). This approach advocates the development of communicative competence as a main goal through the extensive use of the target language as a mean of communication during the classroom sessions. Since the concept of CLT is taken from the West, it might be ill-suited to EFL contexts because of misunderstandings surrounding its theory and practice among EFL teachers. The objective of this paper is to determine the implementation of CLT approach in EFL teaching in Southeast Asia which is commonly reported by English teachers and researchers literally. The findings of the study provide pedagogical implication for EFL classroom practices.